2015
DOI: 10.1016/j.juro.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Improved Split Renal Function after Percutaneous Nephrostomy in Young Adults with Severe Hydronephrosis Due to Ureteropelvic Junction Obstruction

Abstract: Split renal function detected by renography may not accurately predict recovered, poorly functioning kidneys, especially in young adults. First observing the recoverability of hydronephrotic kidneys by percutaneous nephrostomy drainage and then preserving select kidneys may be an effective method to manage poorly functioning kidneys due to ureteropelvic junction obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 16 publications
2
22
0
1
Order By: Relevance
“…Radionuclide renography is the most commonly used method, but it is difficult to evaluate the outcomes at different follow-up times using this technique [12,13]. A PCN catheter should remain inserted for about 4-12 weeks [1], but patients with PCN drainage are at increased risk of further renal function loss and infection [4,11]. Transforming growth factor-β and urinary tubular enzymes have also been used to predict the recoverability of renal function after the relief from obstruction, though the efficacy and feasibility of these biological agents need further evaluation [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Radionuclide renography is the most commonly used method, but it is difficult to evaluate the outcomes at different follow-up times using this technique [12,13]. A PCN catheter should remain inserted for about 4-12 weeks [1], but patients with PCN drainage are at increased risk of further renal function loss and infection [4,11]. Transforming growth factor-β and urinary tubular enzymes have also been used to predict the recoverability of renal function after the relief from obstruction, though the efficacy and feasibility of these biological agents need further evaluation [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…However, the kidneys in children are still developing, allowing the potential for renal function to recover after removal of obstruction in children, even in the case of severe obstruction [18]. It is usually diagnosed early because of its obvious symptoms, and is thus often mild when diagnosed, and the potential recoverability of renal function in adults is therefore also often favorable [1,10,13]. However, Zhang et al [1] found that age still played an important role in postoperative improvement of renal function, even among adult patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…üreteropelvik darlığa bağlı ciddi hidronefrozu ve bölünmüş renal fonksiyonu %10'un altın-da olan 53 hastaya PKN takmışlar ve 29 genç erişkinin 24'ünde (%82.8) bölünmüş böbrek fonksiyonlarında düzelme görmüşler [1]. Diğer taraftan toplayıcı sistem dışına idrar kaçağı ile birlikte olan non-obstrüktif üropatiler enfekte ürinom, retroperitoneal abse, pyelonefrit, peritonit ve ürosepsis gibi ciddi komplikasyonlara yol açabilir [1]. PKN bu durumların hepsinde hem ağrının giderilmesi hem de enfeksiyonun önlenmesi için ideal girişimdir.…”
Section: Introductionunclassified